Keeping Perspective in Academic Leadership Roles: Insights from the Rectors of Icelandic Universities - Kolbrún Arnardóttir 1986- (2015)
Since the position of ‘rector’ is the highest in Icelandic universities, taking over such a role is a major challenge as well as a sensitive change process for the individual and for the organisation. This paper introduces a change leadership model, i.e., the Oroboros Leadership Model. The research questions are: (1) Is it possible to provide academic leaders with a tool or a method that helps them guarantee their success in socializing within their university and to be better able to implement their vision? (2) Is academic leadership different from leadership in other contexts? (3) Is managing/leading universities different than managing/leading other organisations? To answer these questions, a qualitative research was conducted in which all university rectors in Iceland were asked questions about themselves, universities and the Oroboros Leadership Model. The conclusion is that a change leadership model like the one introduced in this paper could be very beneficial to leaders as they take on their new roles. Efnisorð: Change management, Change leadership, Academic leadership